2016
DOI: 10.1177/0042098015596923
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the influence of space and time effects on time on the market

Abstract: This paper is concerned with spatial effects of time on the market for residential property and time varying relationships using a dataset of properties from the Adelaide metropolitan area, Australia, during the period 2002-2011. The analysis firstly considers the spatial dependence in time on the market and secondly extends the analysis to a space-time model using 2SLS regression. The findings demonstrate the complexity in spatial analysis with results indicating a random distribution of time on the market in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Spatial patterns in house prices and crime variables arguably are best established using Moran's I and Local Indicator Spatial Association (LISA) models which enable variation of spatial dependence between two variables to be studied. More widely in the real estate sector, (McGreal et al, 2015) have the benefits of utilizing these techniques and specifically in the crime sector Zhang and McCord (2014) provide a useful illustration of the application of this type of spatial analysis in establishing relationships between foreclosures and crime rates in the Louisville Metro (Kentucky, USA). In the case of Seattle, Matthews et al (2013) utilizing Moran's I identified localized spatial effects for different types of crime.…”
Section: Spatial Analysis Of Crime Variablesmentioning
confidence: 99%
“…Spatial patterns in house prices and crime variables arguably are best established using Moran's I and Local Indicator Spatial Association (LISA) models which enable variation of spatial dependence between two variables to be studied. More widely in the real estate sector, (McGreal et al, 2015) have the benefits of utilizing these techniques and specifically in the crime sector Zhang and McCord (2014) provide a useful illustration of the application of this type of spatial analysis in establishing relationships between foreclosures and crime rates in the Louisville Metro (Kentucky, USA). In the case of Seattle, Matthews et al (2013) utilizing Moran's I identified localized spatial effects for different types of crime.…”
Section: Spatial Analysis Of Crime Variablesmentioning
confidence: 99%
“…This area was selected due to Adelaide’s urban character, 1.6 million (median age of 39 years) population in 2016 and 366,090 single detached residential properties on large land parcels within 2689 Statistical Area 1 (SA1) units (the smallest spatial data unit used to disseminate the Australian Population Census results) (Australian Bureau of Statistics, 2018). Adelaide was considered an appropriate geographic scale as it reflected a “contained” housing market characterised by sub-markets (McGreal et al., 2016). The majority of sale transactions were through private treaty with owner occupancy the main tenure, similar to many international jurisdictions.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, housing search behavior is often considered the relationship between TOM and housing transaction price, which has long been investigated by researchers (for example , Miller, 1978;Zuehlke, 1987;Haurin, 1988;Kalra and Chan, 1994;Forgey et al, 1996;Kramer, 1999;Ong and Koh, 2000;Knight, 2002;Merlo and Ortalo-Magne, 2004;Li, 2004;Hui et al, 2012;Haurin et al, 2013;Khezr, 2015;McGreal et al, 2016;Liang et al, 2018). In the following part of the review, the selected papers are from the perspective of the determinants of TOM, which is by no means exhaustive.…”
Section: Search Behavior In Housing Markets: An Overviewmentioning
confidence: 99%
“…The exceptions are some recent studies (e.g. McGreal et al, 2016;. McGreal et al (2016) examined the spatial effects of TOM on property markets in Adelaide, Australia.…”
Section: Search Behavior In Housing Markets: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation